Population Projection under Changing Fertility Conditions - Aryal, Tika Ram (Journal of Institute of Science and Technology, 2015)
This paper attempts to derive model for population projection under gradual change in fertility schedule on stability conditions using birth trajectory at time t for 0 < t ? a . The projected population can be obtained when the data of the rate of natural increase, net reproduction rate, age variance of the net maternity function, birth rate of the initial stable population along with its age distribution are available of the population. Journal of Institute of Science and Technology, 2014, 19(2): 86-88